Bis-2'-hydroxychalcone and its Complexes as Potential Dye Sensitizer for Dye-sensitized Solar Cell Application - Teo, Kien Yung (Universiti Malaysia Sarawak(UNIMAS), 2018)
In this study, the power conversion efficiency of bis-chalcone derivatives and its complexes as the dye sensitizer in dye-sensitized solar cell had been determined. A total of 6 compounds of bis-chalcone derivatives, namely, compound 1A, 1B, 2A, 2B, 3A and 3B had been synthesized by the Claisen-Schmidt condensation reaction. Two compounds, compound 1B and compound 2B were further proceeded to the complexation with cis-dichlorotetrakis(dimethylsulfoxide) ruthenium(II) precursor to yield the complex CX1 and complex CX2. The molecular structure of the synthesized compounds and complexes were characterized and confirmed by the fourier transform infrared spectrophotometer, proton and carbon nuclear magnetic resonance spectrometer, UV-visible spectrophotometer and CHN analysis. Finally, all of the synthesized materials were applied as the dye sensitizer in the dye-sensitized solar cell and the power conversion efficiency was measured using the San Ei XES-40S1 Solar Simulator under monochromatic light of air mass 1.5 global (AM 1.5G) with the incident light intensity of 100 mW/cm2. Results showed that compound 1B afforded the highest power conversion efficiency of 0.05 % due to the good dye absorption towards the TiO2 semiconductor with the fill factor value of 51.60 % recorded. On the other hand, both ruthenium complexes of CX1 and CX2 showed very low power conversion efficiency value of 2.79 x 10-3 % and 1.68 x 10-3 %, respectively. This may have resulted from the symmetrical molecular framework of the ruthenium complex, which hindered the electron transfer towards the TiO2 semiconductor. Therefore, the intermediate compound 1C can be served as the future prospects to further modify the molecular framework of bis-chalcone derivatives.